High performance work practices and service quality in mid-scale lodging industry - Mary Monica Jiony; Lew, Tek Yew; Geoffrey Harvey Tanakinjal; Daria Gom; Ruth Sikopit Siganul (Medwell Journals, 2016)
The main objective of this research is to examine the important constructs of service quality in its relation to high performance research practice with employee engagement as mediating factor. It attempts to identify the potential gap in the service quality performance in the lodging industry in Sabah, Malaysia. A preliminary study to complement a larger research, this study intends to use quantitative approach. The three-fold potential contributions of this paper include: enriching the literature of strategic Human Resource (HR) and Organizational Behavior (OB) as empirical evidence to the management of lodging industry and the service sector in general and lastly, contributing toward the sustainable and robust performance of the ‘Sabah hospitality service quality performance’.